Knowledge, Attitude and Practice on Prevention of Catheter-associated UTI among Nurses of a Tertiary Care Hospital - K.C., Rashmi; Dhakal, Binita (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Urinary tract infection (UTI) is among the common bacterial infections worldwide and approximately 80% are associated with a urinary catheter. Catheter-associated UTI (CAUTI) has been associated with increased mortality, morbidity, length of hospital stay and the best way of CAUTI prevention is to adhere to recommended guidelines on infection control in the use of a urinary catheter. Methods: A cross-sectional analytical study was conducted among the nurses of college of medical sciences. A total of 160 staff nurses were selected using a probability simple random sampling technique. Data was collected using a self-administered questionnaire for knowledge, Likert scale for attitude, and checklist for practice regarding the prevention of CAUTI. The data gathered was analyzed using both descriptive and inferential statistics in SPSS software. Results: Among the total of 160 participants, most of the nurses 59.37% had moderate knowledge and 16.25% had adequate knowledge towards the prevention of CAUTI. The positive attitude of nurses was 41.88% and the majority of nurses 64.38% had a good level of practice. Also, age (p=0.022), professional qualification (p=0.001), designation (p=0.001), current area of practice (p=0.030) and previous information towards CAUTI prevention (p=0.003) among all the socio-demographic variables were statistically significant with the level of knowledge regarding the prevention of CAUTI. Conclusion: Majority of nurses level of knowledge was not satisfactory and had a negative attitude regarding CAUTI prevention. This indicates that the implementation of an educational program is needed to enhance nurses' knowledge regarding catheter management to improve quality care. Keywords: attitude; catheter-associated urinary tract infections; CAUTI; practice; UTI